PENINGKATAN LIFE SKILL MAHASISWA KIMIA BERORIENTASI CHEMOENTREPRENEURSHIP (CEP) MELALUI PEMBELAJARAN KOOPERATIF STAD - Ersanghono K.; Nanik Wijayati; Kusoro Siadi (Jurnal Penelitian Pendidikan, 2011)
Based on the questionnaire to students UNNES Natural Sciences Department of Chemistry, professor of learning methods are still in the form of lectures and such very boring for students. Moreover, the material is an organic chemistry lecture course, especially the less favored and considered difficult by students because it is abstract, so it needs to be assisted visualization. It is therefore interesting to study as well as creativity and innovation fostering student learning and not so monotonous. The purpose of this study to determine the increase in life skill-oriented students Chemoentrepreneurship (CEP) through the STAD cooperative learning. This research is a class act consisting of three cycles. Each stage consists of planning, implementation, observation, and reflection. The subjects of this study is a student of Chemistry Department of Education UNNES third semester. Focus examined in this study is the increase in life skill students (academic skills). The data obtained and analyzed using descriptive methods to determine the increase in student life skill. From the research, learning classical exhaustiveness increased from stage I (43%), stage II (50%), and stage III (86%). The average score life skill (cognitive aspects) college students increased from cycle I, II, and III, respectively, 71.28; 78.21 and 89.15 .. Based on the results of this study can be concluded that the life skill students can be increased through the STAD cooperative learning-oriented CEP.